Dimensiones de la personalidad y su relación con las tendencias prosociales y la empatía en niños(as) y adolescentes en vulnerabilidad psicosocial - Gómez Tabares, Anyerson Stiths (2022)
Personality dimensions and their relationship with prosocial tendencies and empathy were analyzed in 69 children and adolescents in psychosocial vulnerability (Manizales, Colombia). The Big Five questionnaire, the prosocial tendencies scale and the interpersonal reactivity index were used. Correlations (p<.05) were found between prosocial tendencies: anonymous, emergence, emotional and the dimensions of agreeableness and extraversion. Perspective taking and empathic concern were correlated with agreeableness, conscientiousness and extraversion. Structural equation analysis showed that agreeableness, empathic concern and emotional prosocial tendency provided a predictor effect on prosocial emergence tendency (r2=.51). Conscientiousness, extraversion, prosocial emergence and emotional prosocial tendencies predicted perspective taking (r2=.41). Extraversion, emotional prosocial tendency and perspective taking predict anonymous prosocial tendency (r2=.26). Agreeableness and conscientiousness predict empathic concern (r2=.24).